Coinfection of leptospirosis and coronavirus disease 2019: A retrospective case series from a coastal region in South India. Issue 9 (5th May 2022) - Gupta, Nitin; Wilson, William; Ravindra, Prithvishree; Raghu, Roshini; Saravu, Kavitha
Abstract: During the monsoon season of 2020, the coastal areas of South India were endemic to both leptospirosis and coronavirus disease 2019 (COVID‐19). This study aimed to investigate the clinical features and outcomes of patients infected with both infections. A retrospective review of charts of all patients with COVID‐19 who were also diagnosed with leptospirosis by immunoglobulin M enzyme‐linked immunosorbent assay was undertaken. The clinical features, laboratory report, treatment details, and outcomes of all the included patients were recorded. The collected data were summarized as the frequency with percentage for categorical data and the mean or median for continuous data. Twenty‐four cases of coinfections were admitted between July and November 2020. Most of these patients were categorized as severe COVID‐19 ( n = 15, 62.5%). Acute kidney injury was seen in 79.2% ( n = 19) patients, while raised bilirubin was present in 79.2% ( n = 19) of the patients. All patients had raised C‐reactive protein, while all but one had raised procalcitonin. Thrombocytopenia, leucocytosis, and leukocytopenia were seen in 91.7% ( n = 22), 45.8% ( n = 11), and 12.5% ( n = 3) of the patients. The median duration of hospital stay was 11 (8.25–15) days. A total of 79.2% ( n = 19) of the patients improved and were discharged, while 20.8% ( n = 5) died during the hospital stay. In conclusion, patients with fever and atypical manifestations such as hepatic dysfunction, renal dysfunction, and thrombocytopenia should be evaluated for leptospirosis even if they are COVID positive.